Variability of plasma methadone concentration in opiate dependents receiving methadone: a personalised approach towards optimizing dose - Mohamad, Nasir; Ismail, Rusli; Mohamed Nazar, Nor Ilyani; Tan, Soo Choon; Sim, Hann Liang; Idrus, Ilya Irinaz; Abu Bakar, Nor Hidayah (Intechopen.com, 2012)
1. Introduction 1.1 Methadone and methadone maintenance therapy (MMT): An overview Methadone acts on the opioid receptors and produces many of the same effects of morphine and heroin. In the treatment of opioid dependence, methadone has cross-tolerance with other opioid, including heroin and morphine and a long duration of effect. Higher doses of methadone can block the euphoric effects of heroin, morphine, and similar drugs. As a result, properly dosed methadone patients can reduce or stop altogether their use of these substances. Methadone is a misunderstood drug and ignorance about it is common. Even professionals, physicians and pharmacists who are supposed to be the “guardians” of MMT receive very little training about the very medication that they are responsible for. To compound the issue, addiction is mostly viewed not as a disease and its care is frequently relegated to the lay public, at least until very recently. In Malaysia, addiction has solely been under the charge of “Agensi Anti Dadah Kebangsaan” (AADK), an agency that has mainly adopted a criminal approach to addiction. However, this has recently changed in Malaysia. Addiction is now recognized as a medical illness, under the purview of the medical professionals. Nevertheless, many in the medical profession only have a rudimentary understanding of addiction. Most physicians, pharmacists and nurses receive very little training about addiction and much less regarding methadone. Thus, generally, both medical and other caregivers have very limited knowledge about addiction and much less about methadone. They have generally been taught to approach addiction as a character disorder and administer methadone as a substitute.